Synopsis Purioris Theologiae : Latin Text and English Translation: Volume 2, Disputations 24-42 - Van den Belt, Henk (Texts and Sources Ser., 2016)
This bilingual edition of the Synopsis Purioris Theologiae (1625) provides English readers access to an influential textbook of Reformed Orthodoxy. Composed by four professors at the University of Leiden (Johannes Polyander, Andreas Rivetus, Antonius Walaeus, and Anthonius Thysius), it offers a presentation of Reformed theology as it was conceived in the first decades of the seventeenth century. From a decidedly Reformed perspective, the Christian doctrine is defined in contrast with alternative or diverging views, such as those of Roman Catholics, Arminians, and Socinians. The Synopsis responds to challenges coming from the immediate theological, social, and philosophical contexts. The disputations of this second volume cover topics such as Predestination, Christology, Faith and Repentance, Justification and Sanctification, and Ecclesiology.